Kinetics of orientation processes in nematic liquid crystals in a periodically changing magnetic field - Larionov A.N.; Polivaev O.I.; Mashin V.N.; Zakusilov V.P.; Mashina A.V. (E3S Web of Conferences, 2023)
The method of obtaining a magnetic field, the intensity vector of which moves along a conical surface at different values of the angle between the intensity vector and the axis of rotation of the magnetic field, the values of the intensity and angular velocity of rotation of the magnetic field, is described. An increase in the phase shift between the intensity vector and the director is found with an increase in the angle at the apex of the magnetic field cone. In the studied range of angular velocities of rotation of the magnetic field at angles between the intensity vector and the axis of rotation of the magnetic field less than 60 °, the director moves synchronously with the field. An exponential character of the dependence of the orientation relaxation time, which characterizes the rapid action of liquid crystal technical devices, on pressure and temperature is established.